Epistemological disjunctivism - Pritchard, Duncan (Oxford : Oxford University Press, 2012)
Duncan Pritchard offers an account of perceptual knowledge arguing that it is paradigmatically constituted by true belief that enjoys rational support which is reflectively accessible to the agent. This resolves the issue between intermalism and externalism, and poses a radical challenge to contemporary epistemology.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Knowledge, Theory of; Disjunction (Logic)